Engineering Asset Management 2016 Proceedings of the 11th World Congress on Engineering Asset Management - Zuo, Ming J.; Ma, Lin.; Mathew, Joseph; Huang, Hong-Zhong.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
These proceedings gather selected peer-reviewed papers from the 11th World Congress on Engineering Asset Management (WCEAM), which was held in Jiuzhaigou, China, on 25-28 July, 2016. These proceedings cover a wide range of topics in engineering asset management, including: ·         strategic asset management; ·         condition monitoring and diagnostics; ·         integrated intelligent maintenance; ·         sensors and devices; ·         information quality and management; ·         sustainability in asset management; ·         asset performance and knowledge management; ·         data mining and AI techniques in asset management; ·         engineering standards; and ·         education in engineering asset management. The breadth and depth of these state-of-the-art, comprehensive proceedings make them an excellent resource for asset management practitioners, researchers and academics, as well as undergraduate and postgraduate students.
A Model for Increasing Effectiveness and Profitability of Maintenance Performance: A Case Study -- Maintenance Process Improvement Model by Integrating LSS and TPM for Service Organisations -- Group Replacement Policies for Repairable N-Component Parallel Systems -- Low Speed Bearing Condition Monitoring - A Case Study -- Program Control-Flow Integrity Checking Based Soft Error Detection Method for DSP -- Research on the Fault Diagnosis of Planetary Gearbox -- Bridge Condition Assessment under Moving Loads using Multi-sensor Measurements and Vibration Phase Technology -- EcoCon: A System for Monitoring Economic and Technical Performance of Maintenance -- An Adaptive Power-Law Degradation Model for Modelling Wear Processes -- A Comparison Study on Intelligent Fault Diagnostics for Condition Based Maintenance of High-Pressure LNG Pump -- Rotating machine prognostics using system-level models -- Study on the Poisson's Ratio of Solid Rocket Motor by the Visual Non-Contact Measurement Teleoperation -- Reliability Allocation of Multi-Function Integrated Transmission System Based on the Improved AGREE Method -- A Study of Sustained Attention Improving by Fuzzy Sets in Supervisory Tasks -- Waukesha 70 Gas Engine Failure Investigation -- Construction of Index System of Comprehensive Evaluation of Equipment Maintenance Material Suppliers -- Addressing missing data for diagnostic and prognostic purposes -- Imperfect Coverage Analysis for Cloud-RAID -- Research on Data Analysis of Materiel System Based on Agent Simulation -- Research on the Fault Diagnosis Method of Equipment Functionally Significant Instrument Based on BP Neural Network -- Asset Performance Measurement: A Focus on Mining Concentrators -- Mobile Technologies in Asset Maintenance.- Essential Elements in Providing Engineering Asset Management Related Training and Education Courses -- Optimizing the unrestricted wind turbine placements with different turbine hub heights -- Predicting Maintenance Requirements for School Assets in Queensland -- Research on Armored Equipment RMS Indexes Optimization Method Based on System Effectiveness and Life Cycle Cost -- Dealing with Uncertainty in Risk Based Optimization -- The Design and Realization of Virtual Maintenance and Training System of Certain Type of Tank -- Measures to Ensure the Quality of Space Mechanisms -- A Decision-making Model of Condition-based Maintenance about Functionally Significant Instrument -- Research on the Fault Diagnosis Method of Equipment Functionally Significant Instrument Based on BP Neural Network -- Gearbox Fault Diagnosis Based on Fast Empirical Mode Decomposition and Correlated Kurtosis -- Bulge Deformation in the Narrow Side of the Slab during Continuous Casting.
Keywords: Industrial Management; Technological innovations; Financial services industry; Management; Industrial Management; Innovation and Technology Management; Financial Services; Management